Flow cytometry analysis reveals a decrease in intracellular sodium during sperm capacitation - Escoffier, Jessica (2012)
Mammalian sperm require time in the female tract in order to be able to fertilize an egg. The physiological changes that render the sperm able to fertilize are known as capacitation. Capacitation is associated with an increase in intracellular pH, an increase in intracellular calcium and phosphorylation of different proteins. This process is also accompanied by the hyperpolarization of the sperm plasma membrane potential. Recently, we presented evidence showing that epithelial Na+ channels (ENaC) are present in mature sperm and that ENaCs are blocked during capacitation. In the present work, we used flow cytometry to analyze changes in intracellular Na+ concentration ([Na+](i)) during capacitation in individual cells. Our results indicate that capacitated sperm have lower Na+ concentrations. Using sperm with green fluorescent protein in their acrosomes, it was shown that the lower [Na+](i) concentration only occurs in sperm having intact acrosomes. ENaC inhibition has been shown in other cell types to depend on the activation of cystic fibrosis transmembrane conductance regulator (CFTR). In non-capacitated sperm, amiloride, an ENaC inhibitor, and genistein, a CFTR activator, caused a decrease in [Na+](i), suggesting that also in these cells [Na+](i) is dependent on the crosstalk between ENaC and CFTR. In addition, PKA inhibition blocked [Na+](i) decrease in capacitated sperm. Altogether, these data are consistent with the hypothesis that the capacitation-associated hyperpolarization involves a decrease in [Na+](i) mediated by inhibition of ENaC and regulated by PKA through activation of CFTR channels.